METODE PENGAJARAN KREATIF BERBASIS KRISTEN UNTUK ANAK USIA DINI - Ester Bungin; Ice Pagirik (CV. Adiba Aisha Amira, 2024)
This study aims to explore how creative teaching methods integrated with Christian values can be applied in early childhood education. The main focus of this research is to identify effective strategies for combining Christian values such as love, forgiveness, honesty, and obedience to God with creative learning approaches to shape children's character from an early age. This research employs a qualitative method with a case study approach in several Christian educational institutions that offer curricula based on Christian values.Data were collected through observations and analysis of curriculum documents. The key findings indicate that creative methods such as role-playing, drama, and art projects are highly effective in internalizing Christian values in children. These activities not only help children understand these values conceptually but also allow them to experience and practice them within their daily social contexts. The study also found that integrating Christian values into creative learning can strengthen social relationships among children, enhance empathy, and promote positive behavior.The conclusion of this study is that Christian-based creative teaching can have a significant impact on the character development of young children by combining moral and spiritual values within engaging and interactive learning methods. The implications of this research highlight the importance of developing curricula that consider creativity and the integration of religious values as part of early childhood education.